2016
DOI: 10.1002/ijch.201600104
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of SmI2‐Mediated Reformatsky Reaction for Macrolactam Formation Using a Cyclopropyl Group as a Probe

Abstract: A mechanistic study using a cyclopropylmethyl radical clock as a probe to investigate the formation of a macrolactam ring via an SmI2‐mediated intramolecular Reformatsky reaction is experimentally explored. The results of our study indicate that the key SmIII‐enolate intermediate is formed by cleavage of a C−Br bond in an anion‐mediated β‐elimination, and then eventually undergoes an intramolecular aldol condensation to form the macrolactam ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…EPR analysis of the resulting trapped species support a mechanism in which direct reduction of the carbon–bromine bond results in an α-centered radical rather than a ketyl radical intermediate. While a recent study has shown some experimental support for the presence of ketyl radical intermediates in similar reductions, the substrates for that study contained electronically dissimilar α-bromoamides . Further support that SmI 2 reduction of α-bromoketones proceeds through an α-centered radical was established through spin-trapping studies using deuterium-labeled and differentially substituted substrates.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…EPR analysis of the resulting trapped species support a mechanism in which direct reduction of the carbon–bromine bond results in an α-centered radical rather than a ketyl radical intermediate. While a recent study has shown some experimental support for the presence of ketyl radical intermediates in similar reductions, the substrates for that study contained electronically dissimilar α-bromoamides . Further support that SmI 2 reduction of α-bromoketones proceeds through an α-centered radical was established through spin-trapping studies using deuterium-labeled and differentially substituted substrates.…”
mentioning
confidence: 96%
“…While a recent study has shown some experimental support for the presence of ketyl radical intermediates in similar reductions, the substrates for that study contained electronically dissimilar α-bromoamides. 20 Further support that SmI 2 reduction of α-bromoketones proceeds through an α-centered radical was established through spin-trapping studies using deuterium-labeled and differentially substituted substrates. These studies should facilitate further development of novel carbon−carbon bond forming reactions through the generation of samarium enolates.…”
mentioning
confidence: 99%